การนำมูลฝอยบริเวณสถานที่กำจัดมูลฝอยกลับมาใช้ใหม่ในรูปสารปรับปรุงคุณภาพดิน กรณีศึกษาเทศบาลตำบลปริก จังหวัดสงขลา (THE UTILIZATION OF WASTE AT THE DISPOSAL SITE INTO FERTILIZATION FORMS: A CASE STUDY OF PRIK SUB-DISTRICT MUNICIPALITY, SONGKHLA PROVINCE) - ไวยเจริญ นภารัตน์; มะแซ รอกิ (วารสารมหาวิทยาลัยศรีนครินทรวิโรฒ สาขาวิทยาศาสตร์และเทคโนโลยี, 2019)
การศึกษาการนำมูลฝอยบริเวณสถานที่กำจัดมูลฝอยของเทศบาลตำบลปริก จังหวัดสงขลา กลับมาหมุนเวียนใช้ใหม่ในรูปสารปรับปรุงคุณภาพดินนั้น จากการสอบถามเจ้าหน้าที่ที่เกี่ยวข้องเกี่ยวกับการจัดการมูลฝอยของเทศบาลตำบลปริก และทำการสุ่มตัวอย่างมูลฝอยบริเวณเทกองมูลฝอยกลางแจ้ง (Open Dumping) ที่แบ่งตามลักษณะการเทกองและอายุการทิ้งมูลฝอยที่แบ่งเป็น 3 ช่วง คือ 1. 1-5 ปี 2. 6 เดือนถึง 1 ปี และ 3. น้อยกว่า 6 เดือน พบว่า เทศบาลตำบลปริกมีระบบการจัดการมูลฝอยประกอบด้วยการคัดแยกมูลฝอยระดับครัวเรือนตั้งแต่ต้นทางแหล่งกำเนิดมูลฝอยในครัวเรือน ระหว่างการเก็บขน และปลายทาง ณ สถานที่กำจัดมูลฝอย โดยเฉพาะคัดแยกมูลฝอยอินทรีย์ มูลฝอยอันตราย มูลฝอยทั่วไป และมูลฝอยรีไซเคิล มีปริมาณมูลฝอยรวมเกิดขึ้นเฉลี่ยวันละ 4-5 ตัน มีระบบการรวบรวมและการเก็บขนมูลฝอยโดยใช้รถปิคอัพ และรถไฮโดรลิคอัดท้ายเพื่อรวบรวมมูลฝอยจากชุมชนไปกำจัด ณ สถานที่เทกองกลางแจ้ง โดยขยะอินทรีย์ถูกนำไปหมักทำปุ๋ย น้ำหมักชีวภาพ และทำถ่านชีวมวล ขยะอันตรายถูกรวบรวมไว้เพื่อรอการกำจัดอย่างปลอดภัย ขยะทั่วไปนำไปเทกองกลางแจ้ง ส่วนขยะรีไซเคิลมีการคัดแยกเพื่อนำไปจำหน่าย จากผลการร่อนมูลฝอยบริเวณเทกองกลางแจ้ง 3 ช่วงอายุมูลฝอยพบว่า มีค่าความชื้นระหว่างร้อยละ 19.11-22.78 ค่าความเป็นกรด-ด่างระหว่าง 7.3-8.6 ปริมาณเถ้าระหว่างร้อยละ 61.68-74.69 บริเวณเทกองซึ่งพบขยะทั่วไปมากที่สุดเฉลี่ยร้อยละ 50.56-63.43 รองลงมาคือ มูลฝอยอินทรีย์เฉลี่ยร้อยละ 30.57-40.57 ปริมาณธาตุอาหารหลัก ได้แก่ ไนโตรเจน (Total N) ฟอสฟอรัส (Total P2O5) และโพแทสเซียม (total K2O) มีค่าเฉลี่ยอยู่ในช่วงร้อยละ 0.34-0.92, 1.21-1.87 และ 0.63-1.74 ตามลำดับ ปริมาณโลหะหนัก ได้แก่ ทองแดง ตะกั่ว และสารหนู เท่ากับ 93.35±2.14, 71.86±1.25 และ 3.70±0.28 มิลลิกรัมต่อกิโลกรัม และผลการวิเคราะห์ออกไซด์ของธาตุพบปริมาณ SiO2 มากที่สุดร้อยละ 42.85 รองลงมาเป็น CaO ร้อยละ 13.88 Fe2O3 ร้อยละ 8.19 และ Al2O3 ร้อยละ 6.97 ตามลำดับ หากพิจารณาการนำไปใช้ประโยชน์ในรูปสารปรับปรุงคุณภาพดิน มูลฝอยจากสถานที่เทกองกลางแจ้งอยู่ในเกณฑ์มาตรฐานปุ๋ยอินทรีย์ พ.ศ. 2548 สามารถร่อนและนำมูลฝอยเก่ากลับมาใช้ใหม่ในรูปการหมุนเวียนสารอาหารที่สำคัญต่อการเจริญเติบโตของพืชได้ คำสำคัญ: การนำกลับมาใช้ใหม่ สารปรับปรุงคุณภาพดิน การกำจัดมูลฝอย โลหะหนัก The study of waste utilization into fertilizer forms was conducted at the waste disposal site of Prik Sub-district Municipality, Songkhla Province. From the interview with the authorities responsible for the waste management of Prik, including the random sampling collection of the solid waste at the open dumping site, which was categorized by the nature and the span of waste dumping, namely (1) 1-5 years, (2) 6 months to 1 year, and (3) less than 6 months, it was found that the household waste have been managed and sorted systematically as a whole process; starting from the household origin, during collecting procedure, and finally to the waste disposal site. The waste was sorted as organic waste, hazardous waste, general waste, and recycled waste, which the total amount of waste averages four to five tons per day. The dump trucks and the hydraulic garbage trucks were used in the household waste collection and dumping to the open waste disposal site. In the disposal process, the organic wastes were transformed to organic fertilizer, fermented bio-extract, and biomass charcoal; while the hazardous wastes were compiled for further safe disposal process. For general wastes, they were dumped in the open field; whereas the recycled wastes were sorted for further selling. In addition, from the winnowing and the analysis of physical and chemical properties of the wastes, the result shown that the moisture content of all three categories ranges from 19.11-22.78, the pH value shows from 7.3-8.6, and the ash content value indicates from 61.68-74.96%. In terms of the waste categories, it was found that general wastes were found the most around 50.56-63.43%, followed by organic wastes (30.57-40.57%). The essential nutrients found are nitrogen (total N), phosphorus (total P2O5), and potassium (total K2O), with the average unit ranging from 0.34-0.92%, 1.21-1.87%, and 0.63-1.74% respectively. Regarding to the heavy metals, it was found that there were copper, lead and arsenic. The range is from 93.35 ± 2.14, 71.86 ± 1.25, and 3.70 ± 0.28 mg/kg respectively. Furthermore, the oxide analysis of the substance found SiO2 the highest at 42.85%, followed by CaO at 13.88%, Fe2O3 at 8.19% and Al2O3 at 6.97%, respectively. Considering the use of the fertilizer, the solid waste from the open dumping site is in the 2005 national organic fertilizer standard which can be winnowed and reused in the form of recycled fertilizer that is important for the plants’ growth in the future. Keywords: Recycling, Fertilizer, Waste Disposal, Heavy Metal